Influence of a Microwave Irradiation on the Swelling and Permeation Properties of a Nafion Membrane - Barragán, V.M.; Muñoz, S. (Journal of Membrane and Separation Technology, 2015)
The effect of a microwave irradiation at 2450 MHz on the swelling and permeation properties of a Nafion membrane in water and methanol media has been studied. The influence of the irradiation power and the exposure time has been analyzed. The results found show that the irradiation hardly affects the membrane liquid uptake, but it affects the expansion properties of the membrane. The hydraulic permeability coefficient of the unmodified and the irradiated membranes has been experimentally determined. Higher hydraulic permeability has been obtained for the irradiated membranes in both water and methanol, but the degree of increment in permeability coefficient with microwave depends on kinds of permeation liquid. The results have been discussed considering the degradation effect occurring on the membrane hydrophobic matrix, which affects to the membrane elastic properties.